Impact of Diagnosis-Related-Group (DRG) payment on variation in hospitalization expenditure: evidence from China - Qiaosheng Li; Xiaoqi Fan; Weiyan Jian (BMC, 2023)
Abstract Background Diagnosis-Related-Group (DRG) payment is considered a crucial means of addressing the rapid increases of medical cost and variation in cost. This paper analyzes the impact of DRG payment on variation in hospitalization expenditure in China. Method Patients with chronic obstructive pulmonary disease (COPD), acute myocardial infarction (AMI) and cerebral infarction (CI) in a Chinese City Z were selected. Patients in the fee-for-service (FFS) payment group and the DRG payment group were used as the control group and intervention group, respectively, and propensity-score-matching (PSM) was conducted. Interquartile distance (IQR), standard deviation (SD) and concentration index were used to analyze variation and trends in terms of hospitalization expenditure across the different groups. Results After DRG payment reform, the SD of hospitalization expenditure in respect of the COPD, AMI and CI patients in City Z decreased by 11,094, 4,833 and 4,987 CNY, respectively. The concentration indices of hospitalization expenditures for three diseases are all below 0 (statistically significant), with the absolute value tending to increase year by year. Conclusion DRG payment can be seen to guide medical service providers to provide effective treatment that can improve the consistency of medical care services, bringing the cost of medical care closer to its true clinical value.